AI-Powered Population Health Education: Enhancing Student Awareness in Higher Education - Ahmad, Wazeer (Cognitive Insight in Education, 2026)
Artificial intelligence (AI) is increasingly shaping teaching and learning in higher education, yet its role in population health education remains underexplored. This study examined how AI supports population health education and enhances student awareness in higher education. A qualitative research design was employed to gain an in-depth understanding of students’ perceptions, experiences, and interpretations of using AI tools in learning population health-related topics. Data were collected through semi-structured interviews with university students who had prior experience using AI-based tools for academic purposes. The data were analyzed using thematic analysis. The findings revealed that students used AI to simplify complex concepts, summarize academic materials, and access health-related information more quickly. Participants also reported that AI helped broaden their understanding of population health by increasing awareness of prevention, hygiene, sanitation, and community well-being. At the same time, important concerns emerged, including the risk of inaccurate information, overreliance on AI, and reduced critical thinking. These findings suggest that AI has strong potential to support population health education when integrated carefully and supported by critical guidance. The study contributes to current discussions on AI in higher education by showing that AI can enhance student awareness of population health issues, but its educational value depends on responsible and ethical use.